Time in Service of Orientalism: The Case of Polish Japanomania at the Turn of the Twentieth Century - Łuksza, Agata (Acta Poloniae Historica, 2025)
In this article, I investigate Japanomania – the European and American fascination with Japan from the 1860s to the 1910s – focusing on how Western conceptions of time determined perceptions of Japanese culture. Drawing on Edward Said’s Orientalism and Stuart Hall’s conception of ‘the West’ as a historical construct, I claim that Western understandings of time were instrumental in disseminating Orientalism, framing the East as exotic, static, and timeless. The study centres on Japanomania in turn-of-the-century Warsaw, including the reception of Japanese exhibitions and theatre performances, showing that the modern concept of time was a crucial tool of Orientalism. Specifically, the idea of ‘universal’ time allowed for comparisons between cultures, positioning non-Western societies as inferior and preserving Western hierarchies and narratives. The article demonstrates how Western ideological frameworks influenced Polish cultural identities and shaped local fantasies about Japan and the Orient.